Potato Value Chain: A Climate-Smart Agriculture Approach - An Extension Workers Manual - Ministry of Agriculture, Animal Industry and Fisheries, Uganda (2023)
The manual is designed to assist the reader with information about potato value chain and its management in times of climate change. It is comprised of five chapters with coordinated content as summarized below. Chapter one gives some background and a contextual aspect of potato production in Uganda. It also outlines the importance of potato in the food system. The section further highlights the growth characteristics of the crop and its different growth stages. It illustrates the common varieties grown in Uganda and detailed seed and ware production requirements. The chapter also includes the different potato production constraints and their remedies. Chapter two defines climate change in general and highlights the major causes of climate change. It also describes the major effects of climate change with a bias towards potato production. It gives an overview of climatic changes in Uganda, its risks, and impact. Chapter three explains the potato production constraints due to climate change specifically highlighting socio-economic, environmental, and environmental constraints. Chapter four describes climate smart potato production principles. It gives an overview of climate smart agriculture, the corresponding strategies for potato farming and the opportunities and challenges of CSA potato farming in Uganda. Chapter five introduces and share the economics of potato production. This section discusses record keeping in detail, highlighting the importance of farm records in decision making. The chapter also highlights the characteristics of good records, the different types of key records as well as the cost benefit analysis of potato production.